Factores relacionados con el bajo peso al nacer en el municipio La Lisa, en el período 2010-2014 - Padrón Beltrán, Regla; Garcés Rodríguez, Roberto Antonio (Revista Habanera de Ciencias Médicas, 2016)
Introducción: el bajo peso al nacer es en la actualidad una de las causas de morbimortalidad perinatal y uno de los indicadores para evaluar los resultados de la atención prenatal. Objetivo: determinar los principales factores de riesgos del bajo peso al nacer en recién nacidos del municipio La Lisa. Material y Métodos: se realizó un estudio de casos y controles en el Municipio La Lisa en el período de 2010 a 2014, de las pacientes atendidas en el Hospital Docente "Eusebio Hernández". El universo estuvo constituido por un total de 364 neonatos bajo peso, la muestra del grupo estudio se correspondió con 257 recién nacidos bajo peso y el grupo control fue una muestra aleatoria de 261 casos con un peso igual o superior a 2 500 gr; se excluyó del estudio a aquellas gestantes cuyo parto no se produjo en este hospital y las que aportaron embarazos gemelares; se obtuvo la información por medio de las historias clínicas del Hospital. Se analizaron los datos y se determinó el Riesgo Relativo. Resultados: Los factores de riesgo más frecuentes fueron: la presencia de 2 ó 3 abortos previos al embarazo, las enfermedades asociadas al embarazo como son la Anemia, Sepsis Urinaria y Vaginal; se demostró la asociación significativa de la aparición del recién nacido bajo peso y los trastornos hipertensivos. Conclusiones: los recién nacidos bajo peso siguen mostrando un incremento en el área de salud, e inciden como factores de riesgo frecuente: la anemia, la sepsis tanto vaginal como urinaria y la hipertensión arterial. Palabras clave: recién nacidos, bajo peso al nacer, factores de riesgo, trastornos hipertensivos, embarazo. ABSTRACT Introduction: low birth weight (LBW) has been considered as one of the most important cause of perinatal morbidity and mortality doing one of the indicator used to assess the results of prenatal health attention quality. Objective: Identify the main risk factors of low birth weight and whether there was an association between the occurrence of low birth weight and Arterial Hypertension in the Municipality. Material y Methods: a study of cases and controls was performed in the municipality La Lisa in the period from 2010 to 2014 in order to identify the main risk factors of low birth weight and whether there was an association between the occurrence of low birth weight and Arterial Hypertension in pregnant women living in the municipality who were treated at the Maternal University Hospital Eusebio Hernandez. The universe consisted of a total of 423 infants underweight, the study group sample corresponded to 257 LBW and the control group was a simple random sample of 261 cases with a weight equal to or greater than 2500 gr. obtained from the same area of health, the study excluded those pregnant women whose delivery did not occur in the previous Hospital and who contributed twin pregnancies, the information was obtained through medical records from the Hospital. Data determined for each of the Relative Risk factors were analyzed. Results: Risk factors that affected were: the presence of 2 or 3 pre-pregnancy abortions, pregnancy-associated diseases such as anemia, urinary Sepsis, Sepsis Vaginal, the significant association of the appearance of the underweight newborn were also demonstrated and also the hypertensive disorders of pregnancy. Conclusions: the municipality to maintain the increase of low birth weight, risk factors that affected were: the anemia, the presence of 2 or 3 pre-pregnancy abortions, urinary and vaginal sepsis, and also hypertensive disorders of pregnancy. Key words: low birth weight, newborn, risk factors, hypertension disorders, pregnancy.